Effect of regenerator on V-type alpha Stirling engine performance - Varit Senviboon; Panya Kansuwan; Banterng Silpsakoolsook; Sutapat Kwankaomeng (My University, 2021)
This paper presents the performance of an Alpha-type Stirling engine with and without a regenerator. The Alpha Stirling engine with a V-cylinder arrangement has two pistons that fit in hot and cold cylinders separately. The prototype engine has swept volume of 79 cm3. Working gas is ambient air and coolant is water. The engine performance test was conducted in two operating modes as a heat pump and a heat engine. Working as a heat pump, temperature drop at the cold cylinder was measured relative to work input from an induction motor. By varying its speed using an inverter, the cooling curves of the engine with and without regenerative heat exchanger were obtained for comparison. Working as a heat engine, on the contrary, heat input instead of work input as in the heat pump was applied to the engine by a fuel burner at a constant feed rate of LPG. The temperature on the cold cylinder is controlled by cooling water from the cooler. By varying the cooling water temperature, the variations of work output were measured from the output shaft by the rope brake dynamometer. The performance results of the two operating modes with and without regenerator were compared.
Keywords: Stirling cycle; Alpha (finance); Advanced Thermodynamic Systems and Engines